Variation in cost and performance of routine immunisation service delivery in India. Issue 3 (22nd June 2018) - Chatterjee, Susmita; Das, Palash; Nigam, Aditi; Nandi, Arindam; Brenzel, Logan; Ray, Arindam; Haldar, Pradeep; Aggarwal, Mahesh Kumar; Laxminarayan, Ramanan
Abstract : A comprehensive understanding of the costs of routine vaccine delivery is essential for planning, budgeting and sustaining India's Universal Immunisation Programme. India currently allocates approximately US25 per child for vaccines and operational costs. This budget is prepared based on historical expenditure data as information on cost is not available. This study estimated the cost of routine immunisation services based on a stratified, random sample of 255 public health facilities from 24 districts across seven states—Bihar, Gujarat, Kerala, Meghalaya, Punjab, Uttar Pradesh and West Bengal. The economic cost for the fiscal year 2013–2014 was measured by adapting an internationally accepted approach for the Indian context. Programme costs included the value of personnel, vaccines, transport, maintenance, training, cold chain equipment, building and other recurrent costs. The weighted average national level cost per dose delivered was US2.29 including vaccine costs, and the cost per child vaccinated with the third dose of diphtheria–pertussis–tetanus (DPT) vaccine (a proxy for full immunisation) was US31.67 (at 2017 prices). There was wide variation in the weighted average state-level cost per dose delivered inclusive of vaccine costs (US1.38 to US2.93) and, for the cost per DTP3 vaccinated child (US20.08 to US34.81). Lower costs were incurred by facilities and districts that provided the largest number of doses of vaccine. Out of the total cost, the highest amount (57%) was spent on personnel. This costing study, the most comprehensive conducted to date in India, provides evidence, which should help improve planning and budgeting for the national programme. The budget generally considers financial costs, while this study focused on economic costs. For using this study's results for planning and budgeting, the collected data can be used to extract the relevant financial costs. Variation in cost per dose and doses administered across facilities, districts and states need to be further investigated to understand the drivers of cost and measure the efficiency of service delivery.